Effectiveness of Life Skills Training in Reducing Neurosis Symptoms in Women - Maryam Safara; Zahra Saeedi; Pooya Jafari Doudaran (Journal of Social Behavior and Community Health, 2022)
Background: Neurotic people have intense and continuous emotional sensitivity to others and avoid expressing their feelings. Because of the low level of ego power, they are easily overcome by their emotions and are unable to adapt their behavior to various situations. Training the life skills improves psycho-social abilities which can empower individuals to deal with conflicts and contradictions of life. Methods: This study determined the effectiveness of training programs of life skills to reduce the symptoms of neurosis in married women living in deprived areas of Isfahan, in 2017. To achieve this end, a clinical trial was conducted using pretest-posttest and control group. Among all married women living in deprived areas of Isfahan, 40 individuals who acquired the highest scores in assessment of neurosis by NEO Five-Factor Personality Inventory-short Form were selected and randomly divided into two experimental and control groups (20 people per group). Life skill training was performed for experimental group for 8 sessions, one session per week, each session lasting 2 hours. Data were analyzed with SPSS using descriptive statistics (Mean and standard deviation) and inferential statistics (ANOVA, Analysis of covariance). Results: The results of analysis of covariance showed that life skill training program significantly reduced the symptoms of neurosis among women (P<0.005). Such a change was not seen in women in the control group. Conclusions: Findings of the study reflect the efficacy of life skills training on diminishing neurosis symptoms in women.